(untitled) (Research, Society and Development, 2023)
Hearing loss is a public health problem, which affects approximately 40% of people aged 55-74 years. The main clinical management intervention is hearing aids, however, many people do not use them. This study aimed to evaluate the impact of Individual Personal Sound Amplification device on the quality of life of patients enrolled in the Hearing Health Program at the Hospital Universitário Bettina Ferro de Souza (HUBFS). It is an analytical-descriptive, cross-sectional study. It was carried out at the HUBFS, from August to October 2022. Sociodemographic information was collected from the patients. An adaptation of the self-assessment questionnaire for hearing aids, the International Outcome Inventory for Hearing Aids (IOA-HA), was used. The sample consisted of 59 patients, 55.9% female, aged between 7 and 97 years. About 39.0% had completed high school. Most participants said they used the device for more than 8 hours a day. Overall, the evaluation of the IOA-HA questionnaire showed a range of 75.7% and mean of 3.8 (*p < 0.0001) in the patient’s quality of life. And 69.5% were classified with Upper Low income. It is concluded that there is a compromise on the part of the patient regarding the use of hearing aids. Adherence to the use of hearing aids reflects the self-recognition of hearing loss and the need to use technology for rehabilitation. However, there is a need to propose user empowerment strategies regarding their relationship with the hearing aid.